Social Cataloguing Sites: Features and Implications for Cataloguing Practice and the Public Library Catalogue - Spiteri, Louise F. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
International Standard Bibliographic Description elements were used to evaluate the contents of 16 social cataloguing sites’ records. The heuristics Communication, Identity, and Perception were applied to the sites’ social features. While record content was poor, the social features create a community of interest where people can share their reading interests with one another. Des éléments de la description bibliographique internationale normalisée (ISBD) ont été utilisés pour évaluer le contenu de fiches de 16 sites de catalogage social. Les règles heuristiques Communication, Identité et Perception ont été appliquées aux caractéristiques des sites sociaux. Bien que le contenu des fiches était de mauvaise qualité, les fonctions sociales ont créé une communauté d'intérêt où les gens peuvent partager leurs intérêts de lecture.